Integrative taxonomy reveals two sympatric species of the genus Eucriotettix Hebard, 1930 (Orthoptera: Tetrigidae) - Tan, Ming Kai; Storozhenko, Sergey Yu; Hwang, Wei Song; Meier, Rudolf (Zootaxa, 2017)
Limno-terrestrial pygmy grasshoppers are mostly recognised using morphology but characters used are not always clear-cut for species identification. From a faunistic survey in Singapore, Eucriotettix were collected and two new species are identified and described here: E. guentheri sp. nov. and E. simulans sp. nov. This was done by iteratively incorporating morphological, molecular, morphometric, and ecological data. Mitochondrial COI trees, COI cluster analysis, microhabitat preference, and morphometric analyses provide strong enough indirect evidence that the specimens comprise a pair of species. A key to species of Eucriotettix from Singapore is also provided.